2015
DOI: 10.1021/acs.inorgchem.5b00947
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Luminescence Properties of Lanthanide-Based Polynuclear Complexes Nanoaggregates

Abstract: For the first time, hexanuclear complexes with general chemical formula [Ln6O(OH)8(NO3)6(H2O)n](2+) with n = 12 for Ln = Sm-Lu and Y and n = 14 for Ln = Pr and Nd were stabilized as nanoaggregates in ethylene glycol (EG). These unprecedented nanoaggregates were structurally characterized by (89)Y and (1)H NMR spectroscopy, UV-vis absorption and luminescence spectroscopies, electrospray ionization mass spectrometry, diffusion ordered spectroscopy, transmission electron microscopy, and dynamic light scattering. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 111 publications
2
22
0
Order By: Relevance
“…These experiments suggested that the coordination polymers were solvated by glycerol molecules (GLY). This phenomenon has previously been observed with ethylene glycol for polyoxometalates,32 gold nanoparticles,33 and lanthanide complexes,8 but, to the best of our knowledge, this is the first time that it has been observed for lanthanide‐based coordination polymers. The solvated nanoparticles are hereinafter denoted by [Tb 2 (bdc) 3 ⋅ 4 H 2 O] ∞ @GLY and [Eu 2 (bdc) 3 ⋅ 4 H 2 O] ∞ @GLY.…”
Section: Resultssupporting
confidence: 68%
“…These experiments suggested that the coordination polymers were solvated by glycerol molecules (GLY). This phenomenon has previously been observed with ethylene glycol for polyoxometalates,32 gold nanoparticles,33 and lanthanide complexes,8 but, to the best of our knowledge, this is the first time that it has been observed for lanthanide‐based coordination polymers. The solvated nanoparticles are hereinafter denoted by [Tb 2 (bdc) 3 ⋅ 4 H 2 O] ∞ @GLY and [Eu 2 (bdc) 3 ⋅ 4 H 2 O] ∞ @GLY.…”
Section: Resultssupporting
confidence: 68%
“…These experiments suggestedt hat the coordination polymersweresolvated by glycerol molecules (GLY). This phenomenon has previously been observed with ethylene glycol for polyoxometalates, [32] gold nanoparticles, [33] and lanthanide complexes, [8] but, to the best of our knowledge, this is the first time that it has been observed for lanthanide-based coordination polymers. The solvated nanoparticles are hereinafter denotedb y[ Tb 2 (bdc) 3 ·4H 2 O] 1 @GLYa nd [Eu 2 (bdc) 3 ·4H 2 O] 1 @GLY.…”
Section: Synthesis and Characterization Of The Nanoparticlessupporting
confidence: 69%
“…Lanthanide-based coordinationc ompounds have attracted great attention because of their uniquel uminescenceproperties. [2][3][4][5] The synthesis of tailoredhetero-lanthanide complexes has led to fascinating materials, [6][7][8] but their cost constitutes as eriousd rawback as far as surfacel ighting or the fight againstc ounterfeiting are concerned.M oreover,i n heteronuclear complexes, the number of lanthanide ions is limited and hence also the tuning of their luminescence properties. On the contrary,h eteronuclear lanthanide-based coordination polymers are characterizedb yalarge number of metallic sites even at the nanometrics cale.…”
Section: Introductionmentioning
confidence: 99%
“…assigned to electronic orbital interactions between f-orbitals of the rare-earth metal centres and, in the case of this cluster, the oxygen-centred orbitals of an adjacent oxo-ligand. 42 Such an electrostatic ligand effect could also be observed for the electronic structure of a variety of mono-lanthanide species by Furet et al 38 Hence, the less pronounced splitting in the monomeric complexes 18, 26 and 30 can most likely be assigned as well to such a type of interaction.…”
Section: Paper Dalton Transactionsmentioning
confidence: 69%